PENGARUH SARANA PRASARANA DAN LAYANAN PENDIDIKAN TERHADAP KEPUASAN BELAJAR SISWA YANG DIMEDIASI OLEH MOTIVASI BELAJAR DI SMA NEGERI 3 SEMARANG - Muh Umaryono; Suwito Eko Pramono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning satisfaction is an important indicator of educational quality because it reflects students’ perceptions of learning experiences, facilities, and educational services provided by schools. This study aims to examine the effect of educational facilities and educational services on students’ learning satisfaction, with learning motivation as a mediating variable, at SMA Negeri 3 Semarang. This research employed a quantitative approach using a survey method. The population consisted of 1,290 students, and a sample of 306 students was selected using proportional random sampling. Data were collected through a Likert-scale questionnaire measuring educational facilities, educational services, learning motivation, and learning satisfaction. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test both direct and indirect relationships among variables. The results show that educational facilities have a significant positive effect on students’ learning motivation. Educational services also have a significant positive effect on learning motivation. Furthermore, learning motivation significantly influences students’ learning satisfaction. Educational facilities and educational services were found to have a direct and significant effect on learning satisfaction. The mediation analysis indicates that learning motivation partially mediates the relationship between educational facilities and learning satisfaction, as well as between educational services and learning satisfaction. These findings suggest that improving school facilities and strengthening the quality of educational services can enhance students’ motivation, which in turn increases learning satisfaction. Therefore, schools are encouraged not only to focus on physical infrastructure and service quality but also to design learning environments and academic services that actively foster students’ motivation